THE MAXIMUM LIMIT OF LAND OWNERSHIP BY LEGAL ENTITIES BASED ON STATUTORY - Mahfirah, Shara Mitha (Journal Equity of Law and Governance, 2021)
Land is one of the essential elements related to human life. The proverb says, we were created from the ground and will return to the ground. Land issues in the community have influenced land conflicts, namely in the legal dimension, into the economic, political, social and defense and security dimensions. The government needs to establish policies in regulating land tenure as mandated by Law Number 5 of 1960 concerning Basic Agrarian Principles, Article 7 and Article 17. Land tenure can be classified into two legal subjects, namely individuals and legal entities. Regulations regarding land tenure by individual legal subjects have been regulated in detail, unlike land tenure by legal entities. The problem formulation s of this research is how the maximum limit of land ownership by legal entities and how the Rights over land controlled by legal entities. In addition, this research aims to identify and understand the impact caused by over-limit control by legal entities. The method of this research is normative legal research and using several approaches such as legal approach and conceptual approach Therefore, the government's firmness in implementing the UUPA contained in articles 7 and 17 to establish policies in order to achieve optimization of land use for the welfare of the entire Indonesian nation and avoid prolonged conflicts.